PENGARUH PERSEPSI HARGA, INTENSITAS PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA OPTIK FAMILI - Abdul Rahman, Yusuf; Hidayati, Retno (Diponegoro Journal of Management, 2021)
This research aims to analyze the influence of price perceptions, promotion intensity,and service quality on purchase decisions at Optik Famili. The sampling method used on this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 respondents who have purchased a product at least once at Optik Famili. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test, and t test. The result showed that all independent variables: price perceptions, promotion intensity,and service quality has positive and significant influence towards on purchase decisions at Optik Famili.